Copeau and the laboratories of childhood: the games of his children, or rather, le tout rond (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Jacques Copeau's pedagogical project for the renewal of the art of the actor and the theatre drew inspiration from different sources. One of the most important was the childhood, true object of observation and experimentation in at least four occasions which are here designated as "childhood laboratories". In this text, the purpose is to highlight the first of these laboratories, the one that refers to the set of plays and games invented by the three children of Copeau and named by them as le tout rond. The importance of Jacques Copeau's family circle in his theatrical enterprise is evident, and a rich feedback dynamic between life and art can be observed in the context portrayed here.
Keywords: Jacques Copeau; Childhood; Play; Game; Theatrical pedagogy